Assessing Pedestrian Thermal Comfort to Improve Walkability in the Urban Tropical Environment of Nagpur City - Mohite, Shivanjali; Surawar, Meenal (Geographica Pannonica, 2024)
Walking can be an efficient and sustainable mode of transportation for "last mile" connectivity. However, the willingness to walk largely depends on the availability of infrastructure, safety, and comfort. Improving thermal comfort on streets connected to transit stations is crucial for encouraging walking and public transit use. This study assesses seasonal and spatiotemporal variations in pedestrian thermal comfort (PTC) on an N-S-oriented street in Nagpur (India). Thermal walk surveys simultaneously monitored environmental conditions and human thermal perception (thermal sensation vote- TSV). The findings revealed that urban geometry significantly influences PTC and TSV, and the level of influence varied spatiotemporally in both seasons. This study shows the relationship between urban street geometry, microclimate, and PTC, emphasizing the necessity of a multidimensional assessment approach.
Keywords: Walkability; Sustainable Transportation; Microclimate; Pedestrian Thermal Comfort